Impact Of Future Financing Packages on Profitable Growth of MSMEs - Wico Jontarudi Tarigan; Semaria Eva Elita Girsang (Jurnal Ekuilnomi, 2025)
This research aims to determine the effect of future package financing on increasing MSME profits by PT. BTPN Syariah in the working area of ​​Dolok Panribuan District, North Sumatra. This research is a quantitative type of research with a constructivist basis. The population in this study were all respondents who used the future package program by PT. BTPN Syariah in Dolok Panribuan District as many as 1136 respondents. By using the Slovin formula, it is known that the number of samples studied was 60 respondents. The research variables consist of the independent variable, namely the future package and the dependent variable, namely the increase in profits. The measurement technique uses a questionnaire. The research tools used were a future package questionnaire and a profit increase questionnaire, each with 8 statements on a Likert scale. The data requirements tests in this research consist of multicollinearity, heteroscedasticity and regression tests. To find out the research hypothesis proposed using the t test. Based on the results of the t test calculation using the SPSS application above, it is known that the sig value is 0.000 and the calculated t value is 9.786 for variable X1. Based on the t test criteria that have been discussed with a sig level value of 0.05 and the t table value is 2.005, the sig value is smaller than 0.05 or the calculated t value is greater than the t table value so that H1 is accepted so that the future package has an effect on increasing profits MSMEs in Dolok Panribuan District. From the results of the determination test above, it can be concluded that there is an influence of the Future Package on increasing profits. It can be seen that the value of around 62.3% of the influence caused by the Future Package on Increasing Profits and 27.7% is influenced by other variables